Thyroid disorders, epidemiology and outcome among patients in South Western region: Southern Saudi Arabia - Alamri, Abdulrahman M.; Alsareii, Saeed A.; Ali, Yagoub M.; Sultan, Salem A.; Alyami, Mahdi A.; Alswidan, Sammah M.; Alhutaylah, Mahdi A.; Almuntashiri, Ahmed S.; Madkhlai, Rawabi Y.; Hussain, Fatmah A. Al Abu; Alkhamssan, Hadi M.; Alsalaim, Mohammed A.; et al. (International Journal of Research in Medical Sciences, 2020)
Background: Thyroid gland may have a group of a medical condition that affects its main function. The thyroid gland is located at the front of the neck and produces thyroid hormones. The released hormones go through the blood to many body organs for regulating their function, meaning that it is an endocrine organ. These hormones normally act in the body to regulate energy use, infant development, and childhood development. The study aimed to assess the epidemiology of thyroid disorders among cases in the south-western region, Saudi Arabia, and to assess the reporting quality for these cases data. Methods: A retrospective record based descriptive approach was used through reviewing medical records of all cases that were admitted and diagnosed as thyroid related disorders for different indications in the main hospital (king Khalid Hospital) during the period from January 2018 to January 2020. Data extracted throng pre-structured questionnaire including patient's bio-clinical data, preoperative radiological and laboratory investigations. Also, laryngoscope pre and post operatively was reviewed to record findings. Results: The study included 405 cases with thyroid disorders whose ages ranged from 15 to 71 years old with a mean age of 30.5±10.6 years. Females were 82.7% of the included cases, and 83.8% were Saudi. Thyroid related symptoms were recorded for 1-2 years among 58.1% of the cases and for more than 5 years among 15.8%. Thyroid enlargement was recorded for 73.1% of the cases. The multinodular enlargement was recorded for 53.5% of the cases followed with diffuse thyroid enlargement (27.3%). Regarding the type of surgery undergone, total thyroidectomy was the most recorded followed with lobectomy. Conclusions: The study revealed that the majority of the cases were females at middle age presented with benign lesions with Euthyroid status. The most important conclusion was the significant remarkable underreporting of the different clinical data for the cases with many missing items.